MANGLAYDAGI DOG - Muxtorova Sevinch Gʻaybulla kizi (Journals Park Publishing, 2024)
This article analyzes the story “Dog” by the writer Khaliyor Safarov. Some symbolic details in it are commented on, as well as a comparative analysis of image and dialogue motifs with other works.
Keywords: the first sentence, the last sentence, comparative analysis,“Yurt qaygʻusi”, “Aytishuv”, the motive of the conversation